К характеристике царских повинностей в Палестине в первой половине I тыс. до н.э. по данным библейской традиции - ШифМан, И. Ш.
Šifman, I. Š.; Royal service obligations in Palestine in the first half of the first mill, B.C., according to biblical tradition; engl. Résumé S. 48; berücksichtigt auch Ugarit.